Seed Dormancy Release and Germination Requirements of Cinnamomum migao, an Endangered and Rare Woody Plant in Southwest China - Chen, Jing-zhong; Huang, Xiao-long; Xiao, Xue-feng; Liu, Ji-ming; Liao, Xiao-feng; Sun, Qing-wen; Peng, Liang; Zhang, Lan (Frontiers in Plant Science, 2022)
Seed dormancy is a complex adaptive trait of plants that are influenced by several physiological and environmental factors. The endangered plant Cinnamomum migao is also known to exhibit seed dormancy and low germination, which may influence its regeneration; however, these characteristics remain unexplored. To our knowledge, this study is the first to examine the type of dormancy and improve the germination percentage of C. migao seeds. We evaluated the structure and characteristics of the embryo and endocarp of C. migao seeds as well as the effects of endogenous inhibitors. Furthermore, we assessed the effects of light, stratification, alternating temperature, and gibberellic acid 3 (GA3) on the dormancy release of these seeds. The embryo was well developed the endocarp was water-permeable, and no obvious mechanical hindrance to germination was observed. However, the endocarp and embryo contained phenols and other germination inhibitors. The seed extracts of C. migao delayed the germination of cabbage and ryegrass seeds, which indicates the presence of endogenous inhibitors. These findings suggest that C. migao seeds exhibit physiological dormancy. Light and an alternating temperature (15/20°C) did not influence germination. However, GA3 pretreatment, alternating temperatures, and warm stratification relieved dormancy. GA3 pretreatment combined with the 15°C stratification treatment was most effective in rapidly releasing the C. migao seed dormancy. Our findings may facilitate the storage and conservation of this endangered plant, which is currently underrepresented in ex situ collections.